Additional Insights Into the Role of Osteocalcin in Osteoblast Differentiation and in the Early Steps of Developing Alveolar Process of Rat Molars - da Silva Sasso, Gisela Rodrigues; Florencio-Silva, Rinaldo; de Pizzol-Júnior, José Paulo [UNESP]; Gil, Cristiane Damas; Simões, Manuel de Jesus; Sasso-Cerri, Estela [UNESP]; Cerri, Paulo Sérgio [UNESP] (SAGE Publications, 2023)
This study investigated whether osteocalcin (OCN) is present in osteoblast precursors and its relationship with initial phases of alveolar process formation. Samples of maxillae of 16-, 18-, and 20-day-old rat embryos (E16, E18, and E20, respectively), and 05-, 10-, and 15-day-old postnatal rats (P05, P10, and P15, respectively) were fixed and embedded in paraffin or araldite. Immunohistochemistry for osterix (Osx), alkaline phosphatase (ALP), and OCN detection was performed and the number of immunolabelled cells was computed. Non-decalcified sections were subjected to the von Kossa method combined with immunohistochemistry for Osx or OCN detection. For OCN immunolocalization, samples were fixed in 0.5% glutaraldehyde/2% formaldehyde and embedded in LR White resin. The highest number of ALP- and OCN-immunolabelled cells was observed in dental follicle of E16 specimens, mainly in basal portions of dental alveolus. In corresponding regions, osteoblasts in differentiation adjacent to von Kossa-positive bone matrix exhibited Osx and OCN immunoreactivity. Ultrastructural analysis revealed OCN immunoreactive particles inside osteoblast in differentiation, and in bone matrix associated with collagen fibrils and within matrix vesicles, at early stages of alveolar process formation. Our results indicate that OCN plays a role in osteoblast differentiation and may regulate calcium/phosphate precipitation during early mineralization of the alveolar process:
Keywords: alkaline phosphatase; alveolar process; bone formation; matrix vesicles; osteocalcin; rat embryo